A new multifunctional carbon fiber honeycomb sandwich structure with excellent mechanical and thermal performances. (15th October 2021) - Zhao, Weikai; Liu, Zhengxian; Yu, Guocai; Wu, Linzhi
Highlights: The new fabrication process is proposed for multifunctional carbon fiber honeycomb sandwich structure (MCFHS). The mechanical and thermal theoretical models are derived for predicting the thermal conductivity and compressive strength of MCFHS. The compressive strength of MCFHS is up to 21.2 MPa, and the specific compressive strength is 158 × 10 3  m 2 /s 2 . In comparison with carbon fiber honeycomb structure, the thermal conductivity of MCFHS is up to approximately 9.58 times. The MCFHS has excellent capability of thermal dissipation. Abstract: The poor performance of carbon fiber composite honeycomb structures in thermal conduction is hindering their wider adoption in the high-end heat dissipation field. This paper presents a fabrication strategy for a multifunctional carbon fiber honeycomb sandwich structure (MCFHS) that can effectively dissipate the heat and bear the load. The theoretical models are derived for predicting the thermal conductivity and strength of MCFHS for out-of-plane compression loadings, which show a reasonable agreement with experiment. And experiments for point heat source and surface heat source are designed for researching the thermal dissipation capacity of MCFHS. It proves that MCFHS possess excellent thermal and mechanical performance. And the fabrication strategy has the potential to provide new opportunities for lightweight multifunctional honeycombs.